Monocytic origin of foam cells in human atherosclerotic plaques. - Aqel, N; Ball, R; Waldmann, H; Mitchinson, M (1984)
Foam cells in 4 human atherosclerotic plaques reacted with 3 rat monoclonal antibodies directed against T.200 ('anti-leucocyte common' antibody), HLA-Class II molecules and macrophage cytoplasm, respectively. Smooth muscle cells did not react. The results support the view that foam cells are monocyte-derived macrophages.